The Influence of Higher Education Learning Experience During Covid 19 on the Academic Behavior of Today's Students - Alimni Alimni; Saepudin Saepudin; Alfauzan Amin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to analyze the correlation between students’ experiences of learning during the COVID-19 health protocol period and their academic behavior at Islamic Religious Colleges. The research seeks to identify contributing and inhibiting factors shaping students' academic attitudes under pandemic-induced learning conditions. Methodology: The study employs a mixed-method sequential exploratory design. Quantitative data were collected using questionnaires and analyzed with Pearson’s product-moment correlation, while qualitative data were gathered through interviews, observations, and documentation, followed by thematic analysis to identify key influencing factors. The integration of both approaches provides a comprehensive understanding of the research problem. Main Findings: The study reveals a significant correlation between students’ learning experiences during COVID-19 and their academic behavior. Key contributing factors include personal motivation (intrinsic and extrinsic), social support (from peers, family, and educators), an optimized study environment (free from distractions), and tailored learning methods that align with individual preferences. Conversely, inhibiting factors such as environmental disturbances (noise or instability at home) and lack of motivation negatively impacted learning outcomes. A unique finding is that the stressful and uncertain conditions during the pandemic fostered a resilient mindset among students, positively influencing their academic attitudes. Novelty/Originality of the Study: This study uniquely highlights how the challenging learning environment created by the pandemic cultivated adaptive academic behaviors in students. By combining quantitative and qualitative insights, the study offers a detailed understanding of how crisis-driven experiences shape student behavior, providing valuable implications for post-pandemic educational strategies.